Bioinformatics principles and applications - Ghosh, Zhumur (Oxford University Press, 2013)
Bioinformatics principles and applications / Ghosh, Zhumur. -- New Delhi: Oxford University Press, 2013 660.6 G427 No. of Copies : 1